Superharmonic and subharmonic resonances of a carbon nanotube-reinforced composite beam - Alimoradzadeh, M.; Akbas, S. D. (Techno-Press, 2022)
This paper presents an investigation about superharmonic and subharmonic resonances of a carbon nanotubere inforced composite beam subjected to lateral harmonic load with damping effect based on the modified couple stress theory. As reinforcing phase, three different types of single walled carbon nanotubes (CNTs) distribution are considered through the thickness in polymeric matrix. The governing nonlinear dynamic equation is derived based on the von Karman nonlinearity with using of Hamilton's principle. The Galerkin's decomposition technique is utilized to discretize the governing nonlinear partial differential equation to nonlinear ordinary differential equation and then is solved by using of multiple time scale method. Effects of different patterns of reinforcement, volume fraction, excitation force and the length scale parameter on the frequency-response curves of the carbon nanotube reinforced composite beam are investigated. The results show that volume fraction and the distribution of CNTs play an important role on superharmonic and subharmonic resonances of the carbon nanotube reinforced composite beams.
Keywords: carbon nanotubes; composites; couple stress theory; nonlinear vibration; superharmonic and subharmonic resonances